Investigating traffic and controller factors in spatial multitasking: The context of air traffic conflict resolution - Trapsilawati, Fitri; Prastiwi, Pitaloka B.; Vista, Yolla; Myesha, Zara; Herliansyah, Muhammad K.; Wijayanto, Titis (Elsevier, 2021)
Air traffic control (ATC) operations including conflict detection and resolution mainly consist of spatial and multi tasks. The analysis of gender differences in performing spatial and multi tasks in the context of air traffic control remain absent. This study aimed to investigate the influence of traffic factor (i.e., conflict geometry) and controller factor (i.e., gender differences) on the objective and physiological measures of the controllers. Twenty-two college students consisted of eleven male and females, respectively, performed conflict resolution tasks given six different conflict geometries (i.e., crossing, converging, and overtaking conflicts for both level and non-level courses). The results indicated that the effects of gender were absent on the objective measures (i.e., controllers’ performance, workload, and situation awareness) but present on the physiological measure. Gender differences affected beta activation on the left prefrontal (p = 0.027) and right parietal lobes (p = 0.008) where male controllers exhibit higher activation as compared to the female counterparts. These findings offer several implications for conflict resolution in ATC including function allocation and training as well as technological intervention.